Novel rigid rod polymers from a thermal cyclization reaction. (February 2015) - Borbone, Fabio; Tarallo, Oreste; Roviello, Valentina; Caruso, Ugo; Pirozzi, Beniamino; Roviello, Antonio
Abstract : Graphical abstract: Highlights: Novel rigid rod polymers are easily obtained by thermal cyclization of new polyamides. The soluble/meltable polyamides are based on diaminobenzodifurane/terephthaloyl unit. Polyamides show thermotropic liquid crystalline behavior. Oriented films and fibers are easily obtained from melt without drawing. Fibers of cyclized benzodifuroxazinonic rigid rod polymers retain a good orientation. Abstract: A new type of rigid rod polymer is reported, easily obtained by thermal cyclization of a soluble/meltable polyamidic precursor. The polyamides are based on a diaminobenzodifurane monomer and are prepared by polycondensation reaction. The polymers are characterized by NMR, FTIR, GPC, TGA, DSC. The cyclization reaction produces insoluble/unmeltable benzodifuroxazinonic based polymers with rigid rod structure. Due to their thermotropic liquid crystalline behavior the polyamides are easily obtained from melt as oriented films under shear and as fibers by extrusion. High degree of orientation and smectic-like arrangement of polyamides are demonstrated by X-ray fiber diffraction. Retention of the orientation upon cyclization is demonstrated by XRFD, optical and electron microscopy.